Evaluation of urinary podocin and nephrin as markers of podocyturia in dogs with leishmaniosis - Valeria Pantaleo; Tommaso Furlanello; Erika Carli; Laura Ventura; Laia Solano-Gallego (Parasites & Vectors, 2024)
Abstract Background Renal disease is the main cause of death in canine leishmaniosis. Detection of an active glomerular injury is important to identify early renal damage and to prevent the development of chronic kidney disease. Podocyturia can indicate renal injury, and podocyte-associated molecules such as podocin and nephrin can be used to identify podocyturia. The purpose of the study was to evaluate urinary podocin and nephrin concentrations in dogs with leishmaniosis as markers of podocyturia. Methods A total of 35 healthy dogs and 37 dogs with leishmaniosis were enrolled in the study. Dogs with leishmaniosis were classified according to the staging of the International Renal Interest Society (IRIS). Urinary podocin and nephrin concentrations were measured in all dogs with a validated enzyme-linked immunosorbent assay test and normalized to creatinine (uPoC and uNeC, respectively). The demographic, clinical, and laboratory data from both groups were analyzed and compared. Subsequently, the laboratory results were analyzed and compared according to IRIS staging in dogs in IRIS stage I and dogs in IRIS stage II + III + IV. The Pearson’s correlation test evaluated the relationship between urinary markers of podocyturia. Results Compared with healthy dogs, lower urinary podocin [median values (IQR): 15.10 (11.75–17.87) ng/ml versus 8.63 (7.08–13.56) ng/ml; P < 0.01] and nephrin [median values (IQR): 3.2 (3.62–5.43) ng/ml versus 2.67 (2.06–3.44) ng/ml; P < 0.01] were found in infected sick dogs. No significant differences were observed in the uPoC and uNeC between the two groups. Urinary nephrin and podocin concentrations were higher in healthy dogs and in dogs in IRIS stage I (both P < 0.05) compared with dogs in IRIS stages II + III + IV. No significant differences were found for uPoC and uNeC between healthy dogs and dogs with leishmaniosis in different IRIS clinical stages. Conclusions Dogs with leishmaniosis had a low concentration of podocin and nephrin in more advanced IRIS clinical stages, when kidney disease was more severe compared with healthy dogs and dogs in IRIS stage I with mild disease. Urinary nephrin was detectable for the first time in healthy non-infected dogs. Graphical Abstract